Experiences with serology of Plesiomonas shigelloides. 1. O-antigenic structure - Aldová, E (Journal of hygiene, epidemiology, microbiology, and immunology, 1985)
With a set of 30 O-antisera, O-antigens were identified in 80% of 158 Plesiomonas shigelloides strains. Only strains of one serovar (018) regularly contained capsular antigen that caused their inagglutinability in the live state. Two groups of serovars displayed some O-antigenic relationship: 03 and 029; 08, 011 and 012. Each serovar in either group possessed a specific O-antigen and "group-common" minor antigens, which were designated I, II and III. Serovar 017 possessed O-antigen identical with that of Shigella sonnei phase I; this serovar was the most frequent one. Some serovars seemed to be ubiquitous; this was indicated by their wide geographic distribution and findings in man, domestic and feral animals, and water.
Keywords: aglutinace; lidé; Bulharsko; Československo; sérotypizace; Irák; Serotyping; Iraq; Shigella sonnei; Humans; králíci; O Antigens; Agglutination; Kuba; O-antigeny; Německo východní; Vibrionaceae; zvířata; zkřížené reakce; antigeny bakteriální; Animals; Rabbits; Cuba; Cross Reactions; Bulgaria; Antigens, Bacterial; Czechoslovakia; Germany, East